2018
DOI: 10.1007/s12011-018-1286-1
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Neurotoxicity of Arsenic: Involvement of Oxidative Stress and Mitochondrial Functions

Abstract: Over the last decade, there has been an increased concern about the health risks from exposure to arsenic at low doses, because of their neurotoxic effects on the developing brain. The exact mechanism underlying arsenic-induced neurotoxicity during sensitive periods of brain development remains unclear, although enhanced oxidative stresses, leading to mitochondrial dysfunctions might be involved. Here, we highlight the generation of reactive oxygen species (ROS) and oxidative stress which leads to mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 62 publications
1
37
0
Order By: Relevance
“…One study demonstrated that As has a direct effect on oxidative stress and the imbalances of defensive anti-oxidative mechanism and neurotransmitter metabolism in the hippocampus [40]. In addition, perinatal As exposure has a developmental neurotoxicity with abrupt changes in the reactive oxygen species (ROS), oxidative stress, mitochondrial functions and apoptosis in the developing brain [41].…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that As has a direct effect on oxidative stress and the imbalances of defensive anti-oxidative mechanism and neurotransmitter metabolism in the hippocampus [40]. In addition, perinatal As exposure has a developmental neurotoxicity with abrupt changes in the reactive oxygen species (ROS), oxidative stress, mitochondrial functions and apoptosis in the developing brain [41].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important mechanisms involved in the neurotoxicity of As is its ability to cause oxidative stress and mitochondrial dysfunction [29,30]. Arsenic decreased the activities of mitochondrial complexes I, II-III, and IV in the rat brain and increased the levels of reactive oxygen species (ROS) [31].…”
Section: Toxic Mechanismsmentioning
confidence: 99%
“…Since hippocampus plays a pivotal role in learning and memory modulation [39], learning and memory deficits in arsenic-treated animals might be associated with an impaired cholinergic system. Evidence produced by other studies have suggested that arsenic can disturb anti-oxidants, causing oxidative stress in the brain [40][41][42]. Oxidative stress has been shown to inhibit or decrease acetylcholine receptors in the hippocampus and frontal cortex in animals treated with arsenic [43].…”
Section: Discussionmentioning
confidence: 98%